Workshop Keterampilan Interpersonal Digital: Teknologi Bertemu Empati - Rifiyanti, Hafizah; Filda Angellia; Astried Silvanie; Syamsu Hidayat; Dwi Sidik Permana (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
The workshop "Digital Interpersonal Skills: Technology Meets Empathy," held in the Jagakarsa area, demonstrated success in enhancing participants' digital interpersonal communication abilities. The practical approach employed, along with the relevance of the material to participants' daily needs, facilitated their understanding and application of the skills taught. Additionally, the use of technology, such as social media for promotion and registration, effectively reached the intended audience, namely high school students active on digital platforms. However, challenges remain, particularly in maintaining participants' focus during simulation sessions. This issue is likely linked to the multitasking habits commonly observed among Generation Z. These findings highlight the need for greater emphasis on the importance of concentration in communication, both online and face-to-face.